CARCINOMA OF CALL BLADDER - Mohammad, Gul; Rahman, S. Jamil-ur-; zeb, Aurang (Journal of Ayub Medical College Abbottabad, 1993)
ABSTRACT: Seventy eases of Carcinoma of the Gall Bladder were diagnosed in a group of two thousand patients who underwent the Hepatobiliary operations over a period of eleven years (1979-90), in the District Headquarter Teaching Hospital, Abbottabad arc reviewed. The data covering symptoms, preoperative diagnosis, surgical treatment and prognosis were analysed and compared to the similar data in the literature. Both the results and the reasons for high mortality rate were discussed and importance of early diagnosis is stressed.